MICROBIAL CONVERSION OF CASSAVA STEM (Mannihot esculenta) CELLULOSE INTO REDUCING SUGAR BY Trichoderma reesei PK1J2 - Sigit Setyabudi, Afriyanti, Sardjono & (Proceeding of International Congress, 2014)
Cassava stems can be utilized as an alternative energy source to produce bioethanol due to itscellulose content, polysaccharide compound can not directly used by yeast. Therefore, cellulose need to behydrolyzed into monomers prior to tranformation into ethanol by Saccharomyces cerevisiae. Hydrolysiscan be performed by cellulaseâproducing fungi, such as Trichoderma reesei PK1J2 with ammonium sulphateused as nitrogen source. The effect of ammonium sulphate addition to the growth and reducing sugarproduction rate of Trichoderma reesei from cassava stems was investigated. Hydrolysis was conductedwithout pretreatment. Cassava stem was degraded into small pieces with and without addition ofammonium sulphate. The concentration of (NH4)2SO4 were 0%; 0,5%; 1% and 1,5%. During cellulosefermentation of cassava stem, analysis were carried on cellulose enzyme activity, dry matter loss,glucosamine content, and reducing sugar. Initial spore concentration was 106 spores/g of cassava stem.Addition of ammonium sulphate seem to affect the growth but did not affect of reducing sugar productionof Trichoderma reesei, therefore hydrolisis continued without ammonium sulphate addition. Highestlevels of reducing sugars was obtained after three days of fermentation which was 10,828 g/L.Keywords: Cassava stem, Trichoderma reesei, cellulose